2007
DOI: 10.1038/sj.npp.1301398
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Effects of Prenatal and Adolescent Exposure to Tobacco Smoke on Auditory and Visual Attention

Abstract: Prenatal exposure to active maternal tobacco smoking elevates risk of cognitive and auditory processing deficits, and of smoking in offspring. Recent preclinical work has demonstrated a sex-specific pattern of reduction in cortical cholinergic markers following prenatal, adolescent, or combined prenatal and adolescent exposure to nicotine, the primary psychoactive component of tobacco smoke. Given the importance of cortical cholinergic neurotransmission to attentional function, we examined auditory and visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
143
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(159 citation statements)
references
References 63 publications
12
143
1
Order By: Relevance
“…fMRI studies in adolescents suggest associations between MSDP and inefficient recruitment of task-relevant brain regions, including the temporal lobe, hippocampus, and cerebellum during response inhibition, attention, and memory tasks. As well, additive effects of MSDP and current smoking during adolescence were seen on temporal lobe activation (Jacobsen, Slotkin et al, 2007), suggesting that MSDP may potentiate effects of adolescent smoking on brain functional deficits. Of note, however, additive effects of current and prenatal exposure on brain function were in contrast to structural findings, which showed stronger effects of current exposure relative to prenatal exposure and no additive effects of current and prenatal exposure on white matter microstructure.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…fMRI studies in adolescents suggest associations between MSDP and inefficient recruitment of task-relevant brain regions, including the temporal lobe, hippocampus, and cerebellum during response inhibition, attention, and memory tasks. As well, additive effects of MSDP and current smoking during adolescence were seen on temporal lobe activation (Jacobsen, Slotkin et al, 2007), suggesting that MSDP may potentiate effects of adolescent smoking on brain functional deficits. Of note, however, additive effects of current and prenatal exposure on brain function were in contrast to structural findings, which showed stronger effects of current exposure relative to prenatal exposure and no additive effects of current and prenatal exposure on white matter microstructure.…”
Section: Discussionmentioning
confidence: 93%
“…In general, the current body of literature is very small, and although each study involved unique analyses, several of the 11 studies involved analyses within overlapping participant samples (Jacobsen et al, 2006;Jacobsen, Picciotto et al, 2007;Jacobsen, Slotkin et al, 2007;Paus et al, 2008;Toro et al, 2008). Thus, integrated findings are based on only eight unique samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study examined group differences in task-related brain activity, measured with functional magnetic resonance imaging (fMRI) in adolescent smokers with and without the history of PEMCS during the performance of attentional tasks; combined current (smokers) and prenatal exposure was associated with higher fMRI signal in several cortical regions involved in auditory attention (Jacobsen et al, 2007). At a receptor level, another study reported subtle differences in the expression of nicotinic and muscarinic acetylcholine receptors in the brains of 5-to 12-week-old foetuses exposed and nonexposed to maternal cigarette smoking (Falk et al, 2005).…”
Section: Introductionmentioning
confidence: 99%